2022
DOI: 10.3390/cells11040715
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin Impact on Alternative mRNA Transcription in the Porcine Luteal Cells

Abstract: Chemerin participates in the regulation of processes related to physiological and disorder mechanisms in mammals, including metabolism, obesity, inflammation, and reproduction. In this study, we have investigated chemerin influence on alternative mRNA transcription within the porcine luteal cell transcriptome, such as differential expression of long non-coding RNAs (DELs) and their interactions with differentially expressed genes (DEGs), differences in alternative splicing of transcripts (DASs), and allele-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 130 publications
0
10
0
Order By: Relevance
“…The mRNAs levels and transcription-regulatory mechanisms, such as lncRNAs production, alternative splicing of transcripts and promoting the production of transcripts encoded by one of the alleles available in the genetic material, were analyzed to investigate the effect of the early gestation period milieu on porcine AP cells. The in silico analyses were mainly performed according to Paukszto et al [ 162 ] and Makowczenko et al [ 163 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNAs levels and transcription-regulatory mechanisms, such as lncRNAs production, alternative splicing of transcripts and promoting the production of transcripts encoded by one of the alleles available in the genetic material, were analyzed to investigate the effect of the early gestation period milieu on porcine AP cells. The in silico analyses were mainly performed according to Paukszto et al [ 162 ] and Makowczenko et al [ 163 ].…”
Section: Methodsmentioning
confidence: 99%
“…Identification of lncRNAs in the porcine AP cells was performed according to Shen et al’s [ 161 ] multi-stage procedure with modifications [ 162 , 163 ]. Initially, at the filtering stage, t low expression, protein-coding, single-exon and too short transcripts (length < 200 nt) were excluded from the processed dataset.…”
Section: Methodsmentioning
confidence: 99%
“…In porcine luteal cells, r-chemerin treatment altered the expression of biomarkers related to angiogenesis and apoptosis [ 67 ]. The regulatory effects of chemerin on corpus luteum in pigs were further verified by transcriptomic analysis, which showed that chemerin takes part in the processes including steroids and prostaglandins synthesis, inflammatory response as well as luteotropic and luteolytic signals [ 68 , 69 ].…”
Section: Roles Of the Chemerin System In Reproductionmentioning
confidence: 99%
“…Necroptosis also induces luteolysis in humans [25,26], pigs [27], and cattle [28]. In this article, we reviewed recent findings regarding the mechanisms of these three types of PCD and their contributions to luteolysis in mammals, including cattle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ACD contributes to luteolysis in humans [ 17 , 18 ], rats [ 19 , 20 ], goats [ 21 ], pigs [ 22 ], and cattle [ 23 , 24 ]. Necroptosis also induces luteolysis in humans [ 25 , 26 ], pigs [ 27 ], and cattle [ 28 ]. In this article, we reviewed recent findings regarding the mechanisms of these three types of PCD and their contributions to luteolysis in mammals, including cattle.…”
Section: Introductionmentioning
confidence: 99%